Development of a nanofiltration membrane for humic acid removal through the formation of polyelectrolyte multilayers that contain nanoparticles. Issue 17 (8th April 2016) - Ng, Law Yong; Mohammad, Abdul Wahab; Rohani, Rosiah; Hairom, Nur Hanis Hayati
Abstract: Poly(sodium-4-styrenesulphonate) (PSS) and poly(diallyldimethylammonium chloride) have been employed to construct polyelectrolyte multilayers on a polyethersulphone substrate for use in the nanofiltration of humic acid. Self-synthesised Ag2 O and commercial ZnO nanoparticles were incorporated into the multilayers separately, showing increases in the permeability from 7.53 ± 1.83 to 8.39 ± 1.37 and 8.62 ± 1.03 L m −2 h −1 bar −1, respectively, with no significant leaching observed in the permeates. All polyelectrolyte-modified membranes exhibited good film-formation stabilities and high humic acid retention capabilities, which ranged from 93.14 ± 2.43 to 95.57 ± 3.87%. Less humic acid solutes were deposited onto the surface of the polyelectrolyte-modified membrane, which was confirmed through field emission scanning electron microscopy images. The contact angle was reduced from 44.00 ± 3.46° to 39.10 ± 3.47° when the membrane surface was hydrophilised with PSS as the terminating layer.